2013
DOI: 10.1021/ol4026364
|View full text |Cite
|
Sign up to set email alerts
|

Lingzhiols, Unprecedented Rotary Door-Shaped Meroterpenoids as Potent and Selective Inhibitors of p-Smad3 from Ganoderma lucidum

Abstract: (+)-Lingzhiol and (-)-lingzhiol, a pair of rotary door-shaped meroterpenoidal enantiomers, were isolated from Ganoderma lucidum. Their structures were identified by spectroscopic methods and X-ray diffraction crystallography. Lingzhiol bears an unusual 5/5/6/6 ring system characteristic of sharing a C-3'-C-7' axis. Biological evaluation showed that (+)-lingzhiol or (-)-lingzhiol could selectively inhibit the phosphorylation of Smad3 in TGF-β1-induced rat renal proximal tubular cells and activate Nrf2/Keap1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
95
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 18 publications
5
95
0
1
Order By: Relevance
“…G. lucidum is a well-known ARTICLE mushroom that is used extensively in Asia as a super-grade medicine. Biological studies of the chemicals contained in this mushroom have indicated that both of the enantiomers of lingzhiols show potent and selective inhibitory activity towards the phosphorylation of Smad3 in transforming growth factor-b1-induced rat renal proximal tubular cells and activate Nrf2/Keap1 in mesangial cells under diabetic conditions 4 . In light of the important biological activities of lingzhiol-type compounds and their potential application as lead compound for the development of therapeutic agents against chronic kidney disease, there is an urgent need for the development of a synthetic method capable of providing facile access to these materials to allow for detailed studies of their structure-activity relationship.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…G. lucidum is a well-known ARTICLE mushroom that is used extensively in Asia as a super-grade medicine. Biological studies of the chemicals contained in this mushroom have indicated that both of the enantiomers of lingzhiols show potent and selective inhibitory activity towards the phosphorylation of Smad3 in transforming growth factor-b1-induced rat renal proximal tubular cells and activate Nrf2/Keap1 in mesangial cells under diabetic conditions 4 . In light of the important biological activities of lingzhiol-type compounds and their potential application as lead compound for the development of therapeutic agents against chronic kidney disease, there is an urgent need for the development of a synthetic method capable of providing facile access to these materials to allow for detailed studies of their structure-activity relationship.…”
Section: Resultsmentioning
confidence: 98%
“…The structure of 10b was confirmed by X-ray crystallographic analysis. We also investigated the application of our newly developed reaction as a general method for the construction of [4,3,0] ring systems (Table 3). Enynols 15a-19a were prepared and subjected to the optimized reaction conditions to afford the corresponding products 15b-19b in good-to-acceptable yields, bearing two syn-configured vicinal quaternary stereocentres.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations